English Exposure from Digital Media and its Influence on Communicative Competence: Students’ Perspectives and Experiences - EDDY HARYANTO; URIP SULISTIYO; POVI FRANSISKA; IMELDA YOSE (Indonesian Research Journal in Education |IRJE|, 2019)
This research investigated the phenomenon of English language exposure from digital media, which is divided into three media platforms (internet and social media, audiovisual, and audio). The main aim of the research was to find out participants’ perspectives on digital media as language users and digital media’s influences on the participants’ communicative competence. This research was designed as a qualitative research with a phenomenological approach. The data were collected through semi-structured interviews and document reviews. The findings are divided into two main issues. First, the participants’ perspectives on digital media revealed that digital media are divided into two points of views; 1) their functions (providing platforms to integrate language knowledge into language productions, providing blueprints of popular linguistics features, and answering to any questions about all related information), 2) the contents (limitless, authentic, and engaging). The findings of the research suggest that there is an important experience of English exposure found and exercised by the participants from/in all the three digital media. Implications and suggestions are also discussed.